KARAKTERISTIK UKURAN RISIKO DISTORSI - Rusidawati Rusidawati; Aprida Siska Lestia; Saman Abdurrahman (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2022)
Insurance is a risk transfer from the insured to the insurer. In general insurance companies are grouped into two types that life insurance and general insurance. For measure risk in general insurance the method used is using a measure of risk. In the study of risk management, there is one method forming risk measure known a distortion function. The purpose of this study is prove theorems of properties a measure of coherent and consistent risk of distortion. In this study explain the formation of a measure of risk distortion using a distortion function, indicates that if the distortion function is a concave function and shows the consistency of risk distortion measures preserve second order stochastic dominance and show coherence and consistency several of distortion risk measures. The results of this study concave distortion function is a necessary condition and sufficient condition for coherence and a strictly concave distortion function is a necessary condition and sufficient condition for strict ordering consistent with preserve second order stochastic dominance.